The effect of experience, simulator-training and biometric feedback on manual ventilation technique. (May 2017) - Lewis, Rebecca; Sherfield, Cerrie A.; Fellows, Christopher R.; Burrow, Rachel; Young, Iain; Dugdale, Alex
Abstract: Objective: To determine the frequency of provision and main providers (veterinary surgeons, nurses or trainees) of manual ventilation in UK veterinary practices. Furthermore, to determine the variation in peak inspiratory (inflation) pressure (PIP), applied to a lung model during manual ventilation, by three different groups of operators (inexperienced, experienced and specialist), before and after training. Study design: Questionnaire survey, lung model simulator development and prospective testing. Methods: Postal questionnaires were sent to 100 randomly selected veterinary practices. The lung model simulator was manually ventilated in a staged process over 3 weeks, with and without real-time biometric feedback (PIP display), by three groups of volunteer operators: inexperienced, experienced and specialist. Results: The questionnaires determined that veterinary nurses were responsible for providing the majority of manual ventilation in veterinary practices, mainly drawing on theoretical knowledge rather than any specific training. Thoracic surgery and apnoea were the main reasons for provision of manual ventilation. Specialists performed well when manually ventilating the lung model, regardless of feedback training. Both inexperienced and experienced operators showed significant improvement in technique when using the feedback training tool: variation in PIP decreased significantly until operators provided manual ventilation at PIPs within the defined optimum range. Preferences for different forms of feedback (graphical, numerical or scale display), revealed that the operators' choice was not always the method which gave least variation in PIP. Conclusions and clinical relevance: This study highlighted a need for training in manual ventilation at an early stage in veterinary and veterinary nursing careers and demonstrated how feedback is important in the process of experiential learning. A manometer device which can provide immediate feedback during training, or indeed in a real clinical setting, should improve patient safety.